BRAND ANALYSIS AND EVALUATION OF YOFORIA BANDUNG - Samardhya, Kalyana Anjani; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. In December 2016, Yoforia entered the yogurt market with the thought of banishing a paradigm on how drinking yogurt is feminine. This study aims to implement brand audit analysis by Kevin Lane Keller toward Yoforia to remove any gap between what Yoforia wanted to deliver and what its audience think about Yoforia. This research used qualitative research method by interviewing the manager of Yoforia and a few of its target market. This research also used quantitative research method using online questionnaire spread to the intended target market. Brand Dynamics Model is used to analyze quantitative results. The gap between these two perspectives toward the brand will be shown in Gap Analysis and indicates a low performance of Yoforia in branding. Brand performance in customer’s perspective was analyzed using Extended Strategic Brand Mapping analysis and to measure brand equity, this research uses Brand Dynamics Model. After all of the analysis has been done, the research suggests the manager to start forming and redefine a brand-building program for its brand elements along with the content and then creating a marketing communication strategy based on the findings to solve the gap and improve the branding and content marketing strategy of Yoforia. Keywords: Brand Audit, FMCG, RTD, Yogurt Drink, Yogurt Industry